CYTOKINES, LYMPHOCYTE SUBSETS AND NEUTROPHIL PHAGOCYTOSIS ACTIVITY IN YOUNG PUERPERAL WOMEN WITH ENDOMETRITIS - T. E. Belokrinitskaya; Yu. A. Vitkovsky; L. I. Anohova; N. I. Frolova (Acta Biomedica Scientifica, 2012)
Cytokines levels, lymphocyte subsets and phagocytosis activity of peripheral blood neutrophils were studied in young puerperal women (aged 18—26 years). The level of IL-1a, TNFa, IL-8 was significant decrease, the number of CD4+ lymphocytes and immunoregulatory index (CD4+/CD8+) were increase, neutrophils phagocytosis activity rised in patients with puerperal endometritis.